Landscapes of Devils : Tensions of Place and Memory in the Argentinean Chaco - Gordillo, Gastón (Book collections on Project MUSE., 2004)
Landscapes of Devils is a rich, historically grounded ethnography of the western Toba, an indigenous people in Northern Argentina's Gran Chaco Region.